Contagious mortgage default - Øystein Børsum (University of Oslo, Department of Economics, 2010)
This paper analyses the default option typical to American mortgages. Households borrow to buy durable housing, but future house prices are uncertain, and households find it dvantageous to default on their debt if house prices fall sufficiently. A key assumption of the model is that households are relegated to the rental market upon default, and that there is a small pecuniary inefficiency ('iceberg cost') in renting. This leads defaulters to substitute consumption of other goods for housing; that is, the demand for housing falls upon default. Consequently, when some households default, aggregate demand for housing is reduced, hence house prices fall more, possibly inciting other households to default. This complementarity is a source of multiple equilibria, and a price externality. Using a specific case for which an analytical solution can be derived, I show that contagion is possible: it may be that the default of a minority (interpretable as sub-prime borrowers) spreads to a majority (interpretable as prime borrowers).
Keywords: E21; G11; R21; 330; Housing demand; mortgage market; default risk; multiple equilibria; contagion; Immobilienmarkt; Nachfrage; Hypothek; Notleidende Kredite; Zahlungsunfähigkeit; Ansteckungseffekt; Gleichgewicht; Theorie